Clinical Pain and Neuropsychological Functioning in Parkinson’s Disease: Are They Related? - Gwenda Engels; Wouter D. Weeda; Annemarie M. M. Vlaar; Henry C. Weinstein; Erik J. A. Scherder (Parkinson's Disease)
Introduction. Pain is an important nonmotor symptom of Parkinson’s disease (PD). Brain areas such as the hippocampus and the prefrontal cortex play an important role in the processing of pain. Since these brain areas are also involved in cognitive functioning, for example, episodic memory and executive functions, respectively, we examined whether a relationship exists between cognitive functioning and spontaneous pain in PD. Methods. Forty-eight patients with PD and 57 controls participated. Cognitive functioning was measured by a comprehensive battery of neuropsychological tests. Both the sensory-discriminative aspect and the motivational-affective aspect of pain were assessed. Multiple linear regression analyses were performed to assess a relation between cognition and pain. Results. Cognition was related to neither the sensory nor the affective aspect of pain in our sample of PD patients. Variance in pain measures was primarily explained by symptoms of depression and anxiety. Discussion. The difference between the affective and the sensory aspect of pain might be due to the neuropathology of PD, which is mainly present in areas processing the affective aspect of pain. Pain treatment might improve when mood is taken into account. We provide several explanations for the lack of an association between pain and cognition.